Policies to promote marketing and organization innovation in Vietnamese textile and garment enterprises - Nguyen Thi Lan Huong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Vietnam is one of the major textile and garment exporters in the world, but the value is still low, production and business activities of textile and garment enterprises are located at the bottom of the global value chain. Meanwhile, compared to other industries, textile and garment enterprises have not really had a close connection with each other, have not focused on the stages that bring high added value such as design, distribution, easy to negatively affected by external policies. Therefore, innovation and policies to promote innovation in marketing and organization in textile and garment enterprises are essential in overcoming the above disadvantages, thereby gradually improving the effectiveness of innovation. innovation, improving the productivity, quality and competitiveness of enterprises in the domestic market, as well as the international market. Code: 22050902